2014
DOI: 10.1111/jopr.12234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bonding Agent Application Method on Titanium‐Ceramic Bond Strength

Abstract: Titanium-porcelain bond strength was not affected by the use of a bonding agent or its application method when tested by ISO 9693-1 standard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
2
3
0
Order By: Relevance
“…In contrast, the lower bond strengths of the TK groups appear associated with a higher firing temperature, a longer firing time and the non-effect of the bonder application. This assumption was consistent with a previous study, which showed that the TK bonder did not improve the porcelain bond strength to Ti 48) . Accordingly, the high temperature of the firing might progress the excessive oxidation on the Ti surface by the longer firing time.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, the lower bond strengths of the TK groups appear associated with a higher firing temperature, a longer firing time and the non-effect of the bonder application. This assumption was consistent with a previous study, which showed that the TK bonder did not improve the porcelain bond strength to Ti 48) . Accordingly, the high temperature of the firing might progress the excessive oxidation on the Ti surface by the longer firing time.…”
Section: Discussionsupporting
confidence: 93%
“…As far as the chemical bonding at the interface is concerned, in the literature, there is a wide‐ranging debate on the benefits in bonding strength owing to the bonding agents. From the papers that present quantitative results, it is generally postulated that bonding agent increases the bond strength in the case of dental Ti alloys, while there is a small influence (either positive or negative, depending on the specific system) when Co‐Cr casting alloys are used, which is consistent with this study.…”
Section: Discussionsupporting
confidence: 88%
“…Curtis et al applied bonding agent on dental Ti alloy using different methods (powder, paste, and spray) and observed no increase in metal‐ceramic bond strength compared to specimens with no bonding agent . Hussaini et al examined the effect of bonding agent and surface treatment (no surface treatment, airborne‐particle abrasion, and HCl etching) on the 3‐point bonding strength between a low‐fusing porcelain and commercially pure cast titanium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-fusing ceramics with compatible thermal expansion coefficients were recommended for the veneering of Ti frameworks (18). The silicon dioxide (SiO 2 ) concentration on the Ti-ceramic interface also affects the Ti-ceramic bond strength (31,32). To obtain the highest concentration of SiO 2 , a ceramic border was applied to the Ti-ceramic interface.…”
Section: Discussionmentioning
confidence: 99%